THE CHANGES IN SALIVARY PH BY CHEWING BLACK TEA (Camellia sinensis) CANDY CONTAINING THE SORBITOL - Lisa Prihastari; Meva Afinsa Putri (FKG Unlam, 2022)
Background: Tea contains beneficial chemical compounds, one of which is polyphenols. The polyphenols in black tea can inhibit the growth of bacteria and prevent oral infections. Black tea extract has been proven to increase salivary pH, but children do not like it because of its bitter taste. Therefore, innovation is needed by incorporating black tea extract into candy containing sorbitol. Objective: To determine the effectiveness of chewing black tea candy containing sorbitol on salivary pH compared to non-black tea candy in children aged 7-8. Methods: This research is an experimental field study using a single-blind randomized controlled trial with a pretest-posttest control group design. The research subjects were of 42 children aged 7-8 years divided into two groups, the treatment group, and the placebo group, using a simple random sampling technique. A sampling of saliva was carried out before and after chewing hard candy. Monitoring was carried out for approximately 23 days, and pH was measured three times. Measurement of pH using a digital pH meter®. Results: After conducting the research, it can be seen that there is a significant difference between chewing hard candy made from black tea and sorbitol on the changes in salivary pH (p-value = 0.0001). Conclusion: Chewing hard candy made from black tea and sorbitol is likely to help increase salivary pH, and it could be a solution to prevent dental caries in the future. Keywords : Black tea; Dental caries; Hard candy; Salivary pH ; Sorbitol.